Comparação do tratamento crônico com inibidor da síntese de óxido nítrico ou fluoxetina sobre as alterações cardiovasculares e do tipo depressivas induzidas pelo estresse crônico variável em ratos - Almeida, Jeferson de (2014)
Here we compared effects of chronic treatment with the preferential nNOS inhibitor 7- nitroindazole (7-NI) with those evoked by the conventional antidepressant fluoxetine on alterations taken as markers of depression (immobility in the forced swimming test(FST), decreased body weight gain, and increased plasma corticosterone) and cardiovascular changes evoked by the chronic variable stress (CVS) in rats. For this, male rats were exposed to a 14- days CVS protocol while being concurrently treated with either 7-NI or fluoxetine. Fluoxetine and 7-NI prevented increased immobility in the FST induced by CVS and reduced plasma corticosterone in stressed rats. Both treatments also prevented CVS-evoked reduction on depressor response to vasodilator agents and baroreflex changes. Nevertheless, none of pharmacological treatments affected body weight reduction induced by CVS. Furthermore, fluoxetine reduced body weight gain in unstressed animals. Fluoxetine and nNOS blockade also induced cardiovascular changes independent of stress exposure, including increase on cardiac parasympathetic tone, intrinsic heart rate, and vascular sympathetic modulation; reduction in sympathetic activity to the heart and the pressor response to vasoconstrictor agents, and impairment of baroreflex activity. These findings provide evidence that both fluoxetine and 7-NI prevent depression-like behavioural changes and cardiovascular dysfunctions associated with CVS. Furthermore, both pharmacological treatments caused cardiovascular changes that were independent of stress exposure, some being beneficial and other potentially increasing vulnerability to development of cardiovascular diseases. Nevertheless, the body weight reduction induced by fluoxetine treatment is especially important considering the weight loss related to depression.